THE IMPLEMENTATION OF STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) AND AUTHENTIC MATERIALS (AMs) TO IMPROVE STUDENTS’ LISTENING SKILL - Ni'mah, Dzurriyyatun; Ismiatun, Febti; Kurniasih, Kurniasih (Universitas Nusantara PGRI Kediri, 2018)
Abstract This action research focuses on how the integration of Students Team Achievement Divisions (STAD) and Authentic Materials (AMs) can improve students’ listening skill. The researchers believed that STAD and AMs help students to understand spoken English easily. Moreover, STAD allows the students to work cooperatively before they do the test individually, and AMs provide rich context materials. The research was conducted to the students of second semester English Department, University of Islam Malang and was carried out in two cycles. In the first cycle, only 46% of the students achieved the criteria of success, and in the second cycle, the result showed that the 71% of the students scored ≥75. Keywords: listening skill, Student Teams Achievement Division (STAD), Authentic Materials (AMs)